Diphtheria surveillance. Cases reported to the National Epidemiological Surveillance Network (RENAVE) in Spain from 2014 to 2024 (Boletín Epidemiológico Semanal, 2025)
Introduction: Diphtheria is a bacterial disease that primarily affects the upper respiratory tract, with a lethality rate of up to 10%. It is a vaccine-preventable disease. In Spain, the DTP (diphtheria, tetanus and pertussis) vaccine was introduced in 1965, maintaining coverage rates above 95% since 1999. In Spain, diphtheria is extremely infrequent but in the European Union, an increase in the number of diphtheria cases has been registered in recent years, in males mainly associated with migrant reception centres.Method: A descriptive epidemiological study of diphtheria cases reported to the National Epidemiological Surveillance Network (RENAVE) from 2014 to 2024 was carried. The variables included were: age, sex, country of birth, country of importation, strain, clinical manifestation, vaccination status, mortality and contact tracing.Results: In Spain, from 2014 to 2024, 15 cases of diphtheria were reported to the RENAVE. 73,3% were men; 33,3% aged 25 to 44 years, 73,3% caused by C. diphtheriae and 33,3% imported. Hospitalization was required in the 53,3% of the cases, and one death occurred.Discussion: Diphtheria is infrequent in Spain, thanks to high vaccination coverage rates. The data presented show mild cases and a significant number of imported cases. The most common causative agent is C. diphtheriae; however, cases of C. ulcerans of zoonotic origin have been reported. Is crucial to maintain high vaccination coverage rates, updated protocols and active surveillance systems, including reception plans for migrant people.
Keywords: Diphtheria; surveillance; epidemiology. Spanish Epidemiological Surveillance Network